Relationship of Energy and Protein Intake Levels to Nutritional Status - Liberty Putri Dwi Nggeong; Lewi Jutomo; Utma Aspatria (Universitas Nusa Cendana, 2022)
Stunting is a chronic nutritional problem caused by a lack of nutritional intake during the first 1000 days of life which results in stunted physical growth and cognitive development of children. This study aims to study the relationship between energy and protein adequacy levels with nutritional status. The type of research used in this research is analytic observational with a cross-sectional research design. The sample size in this study was 61 of the 866 population of children under five who were selected by proportional random sampling. Analysis using chi-square test. The results showed that the energy adequacy level variable with significant nutritional status (p-value = 0.000 <0.05) and protein adequacy level with significant nutritional status (p-value = 0.000 <0.05). Nutritional problems, namely stunting, need to be prevented by increasing energy and protein intake in toddlers.